Alginate immobilized enrichment culture for atrazine degradation in soil and water system. Issue 4 (3rd April 2017) - Kumar, Anup; Nain, Lata; Singh, Neera
ABSTRACT: An atrazine degrading enrichment culture, a consortium of bacteria of genus Bacillus along with Pseudomonas and Burkholderia, was immobilized in sodium alginate and was used to study atrazine degradation in mineral salts medium (MSM), soil and wastewater effluent. Sodium alginate immobilized consortium, when stored at room temperature (24 ± 5°C), was effective in degrading atrazine in MSM up to 90 days of storage. The survival of bacteria in alginate beads, based on colony formation unit (CFU) counts, suggested survival up to 90 days and population counts decreased to 1/5 th on 120 days. Comparison of atrazine degrading ability of the freely suspended enrichment culture and immobilized culture suggested that the immobilized culture took longer time for complete degradation of atrazine as a lag phase of 2 days was observed in the MSM inoculated with alginate immobilized culture. The free cells resulted in complete degradation of atrazine within 6 days, while immobilized cells took 10 days for 100% atrazine degradation. Further, immobilized cultures were able to degrade atrazine in soil and wastewater effluent. Alginate beads were stable and effective in degrading atrazine till 3rd transfer and disintegrated thereafter. The study suggested that immobilized enrichment culture, due to its better storage and application, can be used to degrade atrazine in soil water system.